2022
DOI: 10.24018/ejmed.2022.4.5.1511
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pathogenicity of Omicron Varian

Abstract: The surge of the Omicron variant has been studied in overall India, Delhi and Mumbai. The increase in the percentage share of the Omicron strain in total registered cases resulted in a surge of daily new infections. The pathogenicity of Original, Delta, and Omicron variants has been compared using the data collected at the Max Healthcare network in India. The Omicron wave was the least severe of all three waves. The third Omicron wave did not cause much damage due to hybrid immunity generated in the population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…There is increasing evidence that Omicron, despite a significantly higher transmissibility and infectivity, shows a significantly lower rate of severe clinical courses compared to previous VoCs, including the Delta variant, i.e., the last VoC before Omicron [70]. Early reports on the lower number of severe clinical outcomes in Africa [1,2] are concordant with published studies from other geographical areas on the Omicron pandemic, such as the UK and USA, and have been confirmed by recent reports covering recent Omicron variants, including BA1 (B.1.1.529), BA2, BA4, BA5, XBB1.5 and EG5.1-all showing higher transmissibility but significantly lower pathogenicity [71][72][73][74][75][76][77][78][79][80].…”
Section: Lower Pathogenicity Of Omicron Compared To Previous Vocssupporting
confidence: 77%
See 1 more Smart Citation
“…There is increasing evidence that Omicron, despite a significantly higher transmissibility and infectivity, shows a significantly lower rate of severe clinical courses compared to previous VoCs, including the Delta variant, i.e., the last VoC before Omicron [70]. Early reports on the lower number of severe clinical outcomes in Africa [1,2] are concordant with published studies from other geographical areas on the Omicron pandemic, such as the UK and USA, and have been confirmed by recent reports covering recent Omicron variants, including BA1 (B.1.1.529), BA2, BA4, BA5, XBB1.5 and EG5.1-all showing higher transmissibility but significantly lower pathogenicity [71][72][73][74][75][76][77][78][79][80].…”
Section: Lower Pathogenicity Of Omicron Compared To Previous Vocssupporting
confidence: 77%
“…Overall, these studies using different Omicron isolates have demonstrated a shift in cellular tropism with attenuated lung disease in rodents and cats, supporting human clinical data [1,2,[71][72][73][74][75][76][77][78][79][80]. Still, the molecular mechanisms responsible for this reciprocal change in tropism in the Omicron variant are not completely defined so far.…”
Section: Lower Pathogenicity Of Omicron Compared To Previous Vocsmentioning
confidence: 55%
“…The Omicron surge in the Indian state of Karnataka has been studied [10] in relation to the % share of the Omicron lineage out of the total infection. To determine the pathogenicity and virulence of all three variants (original Wuhan, Delta, and Omicron), the data from Max Hospital (India) were studied [11]. The Omicron variant was found to be less harmful than the Wuhan and Delta strains when pathogenicity was compared in terms of CFR and hospitalization rate.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of CFR (case fatality rate) and hospitalization rate, the Omicron is less pathogenic than the Wuhan and Delta strains. The data reported from the Max Hospitals (India) of all three pandemic waves were analyzed [10]. The Omicron wave was the least damaging of all three waves.…”
Section: Introductionmentioning
confidence: 99%